Comparison between novel and standard methods for analysis of free fatty acids in milk – Including relation to rancid flavour. (December 2017) - Wiking, L.; Løkke, M.M.; Kidmose, U.; Sundekilde, U.K.; Dalsgaard, T.K.; Larsen, T.; Feilberg, A.
Abstract: A range of analytic methods for quantifying free fatty acids (FFAs) in milk were compared and further correlated to rancid flavour detected by sensory analysis. Proton transfer reaction–mass spectrometry (PTR–MS) and 1 H nuclear magnetic resonance (NMR) spectrometry were introduced as novel methods for quantifying individual short chain FFAs. Gas chromatography–mass spectrometry (GC–MS) combined with in-solution derivatisation was used for quantifying all individual FFAs, and Bureau of dairy industries (BDI), acyl-CoA-synthetase–acyl-CoA oxidase (ACS–ACOD) assay, Fourier transform infrared spectroscopy were used to estimate the total FFA concentration in 28 milk samples. High correlations ( r between 0.76 and 0.86) to rancid off-flavour were found for all analytical methods, and all the individual FFAs were quantitatively inter-correlated. Furthermore, a high correlation was found between PTR–MS and GC–MS quantification of hexanoic acid. For the BDI method, the sensory thresholds rancid off-flavour in farm bulk milk were 1.95 mmol 100 g −1 fat.